STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI JUNGKAT KABUPATEN PONTIANAK - Hardy Tuwuntjaki E.01108147 (FISIP Universitas Tanjungpura, 2013)
In this paper, the authors found that there are three issues in the coastal attractions Jungkat. The third problem is the lack of infrastructure such as roads baiknta into Jungkat Beach attractions, lack of secure so as to interfere with traffic safety and comfort of tourists and lack of promotion of the existence Jungkat Beach attractions. In this thesis, the author would like to know the things that are included in the internal and external factors. Internal factors are the strengths and weaknesses of the Jungkat Beaches and external factors are opportunities and threats owned Jungkat Beach attractions. The things that are included in the internal and external factors that influence the development process Jungkat Beach attractions Pontianak regency. The methods used by the authors in this study is a qualitative method with descriptive research . Results of this study indicate the location of this attraction is a strategic Jungkat Beach , which is located close to the capital of West Kalimantan Province . Only Jungkat Beach attractions should be developed if you want to go ahead and increase revenue . Researchers using analytical models Strength, Weakness , Opportunities , and Threats ( SWOT ) to find the right strategy in the development of attraction Jungkat Beach Pontianak regency . From the SWOT analysis will find the strength , kelematan , opportunities and threats owned Jungkat Beach attractions . Then these four were classified into internal and external factors . Thus it can be found an appropriate strategy to develop attraction Jungkat Beach Pontianak regency . Keywords : development strategy, Attractions, Beaches Jungkat , Factor Internal, External Factors